2015
DOI: 10.1051/0004-6361/201526650
|View full text |Cite
|
Sign up to set email alerts
|

Probing non-polar interstellar molecules through their protonated form: Detection of protonated cyanogen (NCCNH+)

Abstract: Cyanogen (NCCN) is the simplest member of the series of dicyanopolyynes. It has been hypothesized that this family of molecules can be important constituents of interstellar and circumstellar media, although the lack of a permanent electric dipole moment prevents its detection through radioastronomical techniques. Here we present the first solid evidence of the presence of cyanogen in interstellar clouds by detection of its protonated form toward the cold dark clouds TMC-1 and L483. Protonated cyanogen (NCCNH … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 40 publications
9
91
0
Order By: Relevance
“…(ii) Formation (or destruction) routes for HCNH + and HC 3 NH + must be added to the chemical network. Agúndez et al (2015) also came to this conclusion in their study of the ion NCCNH + in the cold dark clouds TMC-1 and L483. In Figure 6.…”
Section: Discussionmentioning
confidence: 81%
“…(ii) Formation (or destruction) routes for HCNH + and HC 3 NH + must be added to the chemical network. Agúndez et al (2015) also came to this conclusion in their study of the ion NCCNH + in the cold dark clouds TMC-1 and L483. In Figure 6.…”
Section: Discussionmentioning
confidence: 81%
“…Our analysis yielded a fractional molecular abundance of 1.4×10 −12 for this species (Table 2). If we assume a [NCCNH + ]/[NCCN] ratio of ∼10 −4 as inferred from the chemical modelling of Agúndez et al (2015), the abundance of NCCN would be 1.4×10 −8 cm −2 .…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Indeed, Eshchenko et al (2002) and Glarborg et al (1998) have shown that the HCCO + NO HCNO + CO could be an important pathway to form or destroy HCNO. The recent detection of unexpected high abundances of HCCO toward cold dark clouds (Agúndez et al 2015) favours this idea. Glarborg et al (1998) also suggested that HCNO could be efficiently recycled to NO through the reaction with OH.…”
Section: Hnco and Isomersmentioning
confidence: 98%